Design and analysis of an efficient QoS improvement policy in cloud computing. Issue 1 (March 2017) - Banerjee, Sourav; Adhikari, Mainak; Biswas, Utpal
Abstract Cloud computing offers the proficiency to use computing and storage resources on a metered basis and reduces the investments in Information Technology domain. This paper highlights a major research issue, i.e., providing good quality of service (QoS) to the cloud users. The QoS is associated with several parameters such as completion time, response time, turnaround time (TAT), waiting time (WT), bandwidth. A new cloudlet scheduling algorithm—improved round robin cloudlet scheduling algorithm—has been proposed which improves the TAT, WT and number of context switching. It enhances the resource utilization. The experimental results are obtained by CloudSim toolkit extending few base classes and compared by classical round robin algorithm.